Antibiotics resistant Escherichia coli isolated from aquatic ecosystems in Palembang, South Sumatra, Indonesia - Marieska Verawaty; NITA APRIANI; LELY RASTI TARIGAN; ENDAH TRI APRIAN; WEMONA CHARISSA LAURENTA; MUHARNI (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Verawaty M, Apriyani N, Tarigan LR, Apriyan ET, Laurenta WC, Apriani N, Muharani. 2020. Antibiotics resistant Escherichia coli isolated from aquatic ecosystems in Palembang, South Sumatra, Indonesia. Biodiversitas 21: 86-97. Antibiotics-resistant bacteria (ARB) are one of the emerging water contaminants currently gaining serious global concern due to their adverse risk to ecosystems, wildlife, and public health. This study determined antibiotics resistant Escherichia coli isolated from aquatic ecosystems in Palembang. Most probable number (MPN) was used for bacterial estimation and the Kirby-Bauer method was used for susceptibility test against antimicrobial agents. The results indicated that 82% of E. coli isolates from 28 sampling sites were resistant to ampicillin, 57% to tobramycin, and 71% to tetracycline. The isolates showed intermediate profile to kanamycin (50%), 57% to cotrimoxazole, 50% to cefixime, and 54% to gentamycin. These isolates still showed sensitivity towards ciprofloxacin (86%) and chloramphenicol (61%). Total coliform (TC) numbers ranged from 0 to >1600 MPN/100 mL. Sampling sites with high MPN values of ?1600 MPN/100 mL were Sekanak watersheds (SW1, SW8, SW11, SW12, SW13, and SW14) followed by SW2 and SW9 with a value of 1600 MPN/100 mL, while samples from cattle and fish farms (CW) varied from 0 to 170.000 MPN/100 mL. TC of samples collected from retention ponds (RP) ranged from 0 (RPJSC) to 1.600.000 MPN/100 mL (RPSH3). The Escherichia coli (EC) counts varied from 1.7 x 103 (RPSH2) to ?1.6 × 104 MPN/100 mL (SW11, SW12, SW13, and SW14). Several samples (SW3, RPPI, RPTS, RPSB, RPIBA, and RPOPI) have no E. coli. The results indicated some of the sampling locations that exceeds the quality standard of water have been regulated by the Governor of South Sumatra and the Indonesian Government.